Efficacy of Topical Recombinant Human Epidermal Growth Factor for Treatment of Diabetic Foot Ulcer: A Systematic Review and Meta-Analysis. (June 2016) - Yang, Shaowei; Geng, Zhijun; Ma, Kui; Sun, Xiaoyan; Fu, Xiaobing
Diabetic foot ulceration is a major complication of diabetes mellitus. Recombinant human epidermal growth factor (rhEGF) is used topically in the treatment of diabetic foot ulcers. This meta-analysis was designed to evaluate if rhEGF increased the complete healing rate of diabetic foot compared with controls. We searched the MEDLINE, Cochrane Library, EMBASE, and Web of Knowledge databases (up to December 22, 2015). Studies were identified and selected, and data were extracted by 2 independent reviewers. A total of 4 randomized controlled trials including 294 patients were identified. The studies evaluated the rate of healing of diabetic foot that were treated with rhEGF or controls. On account of study heterogeneity, a random-effects model was performed, and the combined odds ratio (OR) indicated a significantly greater complete healing rate in patients treated with rhEGF compared to placebo. The ORs ranged from 1.66 to 14.64, with a combined OR of 4.36 (95% confidence interval = 1.48-12.81, P = .007). These results indicate that rhEGF is efficacious in the treatment of diabetic foot ulcers by increasing the rate of wound healing. These findings support the use of rhEGF in treating diabetic foot.